Habeas data : privacy vs. the rise of surveillance tech - Farivar, Cyrus (Tantor Media, 2018)
An important look at how fifty years of American privacy law is inadequate for today's surveillance technology, from acclaimed Ars Technica senior business editor Cyrus Farivar Until the twenty-first century, most of our activities were private by default, public only through effort; today anything that touches digital space has the potential (and likelihood) to remain somewhere online forever. That means all of the technologies that have made our lives easier, faster, better, and/or more efficient have also simultaneously made it easier to keep an eye on our activities. Or, as we recently learned from reports about Cambridge Analytica, our data might be turned into a propaganda machine against us. In ten crucial legal cases, Habeas Data explores the tools of surveillance that exist today, how they work, and what the implications are for the future of privacy.